Dr. Wan Ali Wan Mamat / Azilah Zainal Abidin @ Ahmad and Norhayatimah Jamil - Abidin @ Ahmad, Azilah Zainal; Jamil, Norhayatimah (2011)
Dr. Wan Ali Wan Mamat was a Director of at National Library of Malaysia who loved to compile Malay Manuscript and art of "Jawi writting',. Dr Wan is a hadrworking person in developing "Jawi writting" through media in Malaysia. He was a very activate person especially related to "Jawi writting". He also made a bigger change when trying to change an old Jawi writting to moden Jawi writting. Besides that he was very interested in "Malay Manuscript" and involved in many related activities. Because of him we could to documentation Malay Manuscript all over the world. He also has implemented many activities to promote a reading habit among people of Malaysia. He tried to encourage people to produce a book. Dr. Wan AH was a person who found a Malay Manuscript in Mekkah. The manuscript is an ancient Malay Manuscript that about almost hundred years. This was a bigger founding by Dr Wan in history. Dr. Wan AH Wan Mamat also has produced a bookentitled "Pemuliharaan Buku dan Manuskrip".